2014
DOI: 10.1111/cge.12481
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effects of genetic markers and the detection of advanced colorectal neoplasias by population screening

Abstract: Genetic markers associated with colorectal cancer may be used in population screening for the early identification of patients at elevated risk of disease. We genotyped 3059 individuals with no cancer family history for eight markers previously associated with colorectal cancer. After colonoscopy, the genetic profile of cases with advanced colorectal neoplasia (213) was compared with the rest (2846). rs2066847 and rs6983267 were significantly associated with the risk of advanced colorectal neoplasia but with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In recent years, PRSs, alone or in combination with ERSs, are increasingly propagated for risk stratification in CRC screening. However, the scores used so far have generally yielded limited ability to distinguish between individuals with and without CRC and its precursors [10][11][12][13] . Jeon et al 11 developed a model including family history, 19 lifestyle and environmental factors, and 63 CRC-associated SNPs identified in genome-wide association studies, which predicted CRC risk with an AUC of 0.63 for men and 0.62 for women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, PRSs, alone or in combination with ERSs, are increasingly propagated for risk stratification in CRC screening. However, the scores used so far have generally yielded limited ability to distinguish between individuals with and without CRC and its precursors [10][11][12][13] . Jeon et al 11 developed a model including family history, 19 lifestyle and environmental factors, and 63 CRC-associated SNPs identified in genome-wide association studies, which predicted CRC risk with an AUC of 0.63 for men and 0.62 for women.…”
Section: Discussionmentioning
confidence: 99%
“…Risk models based on genetic susceptibility loci, alone or in combination with environmental risk factors have been increasingly propagated for risk stratification in CRC screening. However, the models used so far have generally yielded limited ability to distinguish between individuals with and without CRC and its precursors [10][11][12][13] . In recent years, blood levels of microRNAs (miRNAs) have been linked to CRC development 14,15 .…”
mentioning
confidence: 99%
“…Though the functional role of the SMAD7 polymorphisms (rs4464148, rs4939827, and rs12953717) has not yet been interpreted, a number of published epidemiological studies have reported that these polymorphisms are correlated with the risk of developing multiple cancers [ 12 , 28 , 29 ]. However, other studies have reported that these polymorphisms are not associated with cancer development [ 17 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a number of other studies these SMAD7 polymorphisms have been associated with the risk of developing multiple cancers, including CRC [ 12 14 ], renal [ 15 ], and liver cancer [ 16 ]. However, other case-control studies have reported that these polymorphisms are not associated with cancer risk, in CRC [ 17 19 ], breast cancer [ 20 ], and lymphocytic leukemia [ 21 ]. These inconsistencies may be partially due to the relatively small sample sizes in each of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…166 articles were excluded because they clearly did not meet the criteria or were overlapping references (Supplementary Figure 1). A total of 22 eligible studies Jaeger et al 2008;Middeldorp et al 2009;Kupfer et al 2010;Kurlapska et al 2014;von Holst et al 2010;Xiong et al 2010;He et al 2011;Ho et al 2011;Talseth-Palmer et al 2011;Tomlinson et al 2011;Peters et al 2012;Zhang et al 2012;Thean et al 2012;Carvajal-Carmona et al 2013;Talseth-Palmer et al 2013;Wang et al 2013;Hes et al 2014;Hong et al 2014;Yang et al 2014;Zhang et al 2014) were included in the meta-analysis involving 52,657 cases and 85,105 controls. The detailed characteristics of the studies included in this meta-analysis are shown in Table 1.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%